2012
DOI: 10.1007/s11434-012-5317-6
|View full text |Cite
|
Sign up to set email alerts
|

An engraved artifact from Shuidonggou, an Early Late Paleolithic Site in Northwest China

Abstract: Cognition and symbolic thinking are viewed as important features of modern human behavior. Engraved objects are seen as a hallmark of cognition and symbolism, and even as evidence for language. Accumulated evidences including engraved bones, ochre, ostrich eggshells and stone artifacts were unearthed from Africa, Europe, Levant even Siberia Paleolithic sites. But the archaeological evidence for this, including beads, ornaments, burials, performed objects and engraved objects, is rarely discovered in the Pleist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…A number of sequentially marked bones, antlers, shells and stones are reported from Middle and Lower Palaeolithic sites [24, [58][59][60][61][62]. Some were reinterpreted as the result of natural processes [63], few were studied in detail and many are unpublished.…”
Section: Discussionmentioning
confidence: 99%
“…A number of sequentially marked bones, antlers, shells and stones are reported from Middle and Lower Palaeolithic sites [24, [58][59][60][61][62]. Some were reinterpreted as the result of natural processes [63], few were studied in detail and many are unpublished.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of incising abstract patterns on stones either before the knapping process or afterward is rare worldwide (38,39) and, to our knowledge, unique within ISEA (and Sahul)-the closest examples in Asia being a stone core engraved with crossed and parallel lines, which dates to 30 ka in China (40), and five incised stones from Xom Trai Cave in Vietnam (22-19 ka) (41). Similar objects occur in UP France (42) and at Clovis sites (39).…”
Section: Archaeological Backgroundmentioning
confidence: 99%
“…These connections include not just blades but skill in tool manufacture, production of lithic items like finely flaked end scrapers, gravers=piercers and apparently burins, and use of organic items such as the shaft wrench from Murray Springs and beveled base points. Even the line engraved stones from Gault have counterparts and a long history, in the Asian Upper Paleolithic (e.g., Dikov 1996: Figure 4.18v;Peng et al 2012), and the recently reported, if Clovis, Florida mammoth engraving (Purdy et al 2011) also has Asian equivalents (Bednarik 1994:369). These similarities indicate Clovis has relatively recent historical ties to Asia=Alaska and reflects a significant population movement in the Americas even though there is some compelling evidence for earlier or relatively contemporary non-Clovis peoples.…”
Section: Colonizers or Settled-in?mentioning
confidence: 99%